The step 1 is x² + 6x + 8 + 1 = 1, step 2 is x² + 6x + 9 = 1, and step 3 is (x + 3)² = 1. Then the correct option is B.
What is a quadratic equation?
The quadratic equation is given as ax² + bx + c = 0. Then the degree of the equation will be two.
The equation is given below.
x² + 6x + 8 = 0
Convert the standard equation ax² + bx + c = 0 into the form of (x – p)² = q equation.
First, take the coefficient of x, and divide the number by 2.
⇒ 6/2
⇒ 3
Then square the resultant number will be
⇒ 3²
⇒ 9
And add both sides of the equation.
x² + 6x + 9 + 8 = 9
Simplify the equation, then the equation will be
x² + 6x + 9 = 9 – 8
x² + 6x + 9 = 1
We know that the formula of (a ± b)² = a² + b² ± 2ab, then the equation will be
x² + 2 · 3 · x + 9 = 1
(x + 3)² = 1
Then the step 1 is x² + 6x + 8 + 1 = 1, step 2 is x² + 6x + 9 = 1, and step 3 is (x + 3)² = 1.
Then the correct option is B.
More about the quadratic equation link is given below.
https://brainly.com/question/2263981
#SPJ5